Constitutive expression of G-CSF and GM-CSF in human skin carcinoma cells with functional consequence for tumor progression - Müller, Margareta M.; Fusenig, Norbert (International journal of cancer, 1999)
Tumor progression is characterized by an increasing escape of tumor cells from the growth control of their microenvironment, often caused by aberrant expression of growth factors. In the human skin carcinoma model system, based on the HaCaT keratinocyte line, tumor progression to high-grade malignant cells is associated with constitutive expression and secretion of the hematopoietic growth factors G-CSF and GM-CSF in vitro and in vivo. All HaCaT keratinocyte variants express the G-CSF and the GM-CSF receptors at levels comparable to normal keratinocytes. Consequently, they exhibit a stimulation of cell proliferation and migration in culture when treated with these factors. Moreover, both proliferation and migration of the high-grade malignant cells were strongly inhibited by neutralizing antibodies to G-CSF and GM-CSF, respectively. This demonstrates the functional role of these factors in high-grade malignant HaCaT cells through an autocrine mechanism in vitro and implies their significance in tumor progression in vivo. In light of the increasing use of G-CSF and GM-CSF in adjuvant tumor therapy, our data, as well as those disussed for head-and-neck tumors and gliomas, warrant a careful re-evaluation of the clinical application of both factors.
Gesehen am 11.02.2021